Lithium-ion conductivity and crystallization temperature of multicomponent oxide glass electrolytes - Kenji Nagao; Manari Shigeno; Ayane Inoue; Minako Deguchi; Hiroe Kowada; Chie Hotehama; Atsushi Sakuda; Masahiro Tatsumisago; Akitoshi Hayashi (Journal of Non-Crystalline Solids: X, 2022)
Lithium-ion-conducting oxide glass electrolytes in the multicomponent systems Li2O–B2O3–SiO2–P2O5-LiX (LiX = Li3N, Li2SO4, Li2CO3, and LiI) were synthesized using a mechanochemical technique. The crystallization temperature and ionic conductivity of multicomponent glasses with added lithium salts or Li3N were evaluated. Because the crystallization temperature is a measure of the ability of glasses to resist crystallization at high temperature, glasses with high conductivity and high crystallization temperature are desirable electrolytes. In this study, the lithium-ion conductivity of the glasses was found to be correlated with the crystallization temperature, and it was difficult to increase both the conductivity and crystallization temperature. The addition of lithium salts (Li2SO4, Li2CO3, and LiI) increased the conductivity but decreased the crystallization temperature. Nitrogen doping by the addition of Li3N improved both these properties of the oxide glass electrolyte. Therefore, oxynitride glasses are desirable electrolytes owing to their thermal stability and lithium-ion conductivity.